The Evolution of Gamification in TESL: Trends, Innovations, and Future Directions - Karunarathne, Ashmini (International Journal of Language and Literary Studies, 2024)
The Evolution of Gamification in TESL: Trends, Innovations, and Future Directions reviews the body of existing literature on the integration of gamification into Teaching English as a Second Language (TESL). This article explores how game-based elements like points, leaderboards, badges, and narrative-driven tasks have reshaped language learning from traditional methods to interactive, immersive experiences. Drawing on studies that document these developments, the review highlights the positive effects of gamification on learner motivation, engagement, and language proficiency. The review also examines emerging technologies such as Artificial Intelligence (AI) and Virtual Reality (VR), which are transforming TESL by creating personalized and adaptive learning environments. These innovations, as well as mobile learning and micro-learning trends, are discussed as key drivers of accessibility and learner-centered education. The article not only summarizes the benefits but also addresses the challenges highlighted in the literature, including technological disparities, the risk of overemphasizing extrinsic rewards, and the need for adaptable strategies to meet diverse learner needs. In its future outlook, the article considers the evolving role of gamification in TESL, focusing on how content-based instruction and digital platforms will further enhance language learning. This review provides a comprehensive analysis of trends and innovations while offering insights into future research directions that will shape the next phase of gamified language education.